2019
DOI: 10.1002/ece3.5871
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity assessment of tropical shelf eukaryotic communities via pelagic eDNA metabarcoding

Abstract: Our understanding of marine communities and their functions in an ecosystem relies on the ability to detect and monitor species distributions and abundances. Currently, the use of environmental DNA (eDNA) metabarcoding is increasingly being applied for the rapid assessment and monitoring of aquatic species. Most eDNA metabarcoding studies have either focussed on the simultaneous identification of a few specific taxa/groups or have been limited in geographical scope. Here, we employed eDNA metabarcoding to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 94 publications
(144 reference statements)
3
38
0
Order By: Relevance
“…In combination with a traditional visual survey, eDNA allowed for a more comprehensive survey of the biodiversity contained in the Bocas del Toro lagoon. Overall, over 8,500 metazoan OTUs were detected in the eDNA, which is comparable to previous estimates of marine metazoan diversity for the entire Caribbean region (10,676 animal species reported in a 2010 study of georeferenced species records and taxonomic lists 13 ) and is consistent with other eDNA results from the Caribbean 30 . We detected over 200 metazoan OTUs with species-level identifications that had not been previously recorded in the Bocas or OBIS databases.…”
Section: Discussionsupporting
confidence: 87%
“…In combination with a traditional visual survey, eDNA allowed for a more comprehensive survey of the biodiversity contained in the Bocas del Toro lagoon. Overall, over 8,500 metazoan OTUs were detected in the eDNA, which is comparable to previous estimates of marine metazoan diversity for the entire Caribbean region (10,676 animal species reported in a 2010 study of georeferenced species records and taxonomic lists 13 ) and is consistent with other eDNA results from the Caribbean 30 . We detected over 200 metazoan OTUs with species-level identifications that had not been previously recorded in the Bocas or OBIS databases.…”
Section: Discussionsupporting
confidence: 87%
“…At the species level, 52.32% of assignments belonged to organisms of only one super-group, Amoebozoa, which had been the object of remarkable barcoding efforts (e.g., [57][58][59]). All this evidence confirms previous reports that there are major gaps in reference databases that use COI as a marker regarding sediment communities from both marine and freshwater environments [23,60], or even regarding marine organisms in general [33,61]. Notwithstanding, one of the advantages of metabarcoding is that taxonomic identification can only improve as reference databases are updated.…”
Section: Discussionsupporting
confidence: 87%
“…However, Jeunen et al (2019) demonstrated that eDNA was able to discriminate diverse marine habitats within a small spatial scale subject to tidal and water currents. Indeed, some studies have already shown that eDNA surveys are able to detect fine-scale community composition patterns in heterogeneous aquatic habitats (Port et al, 2016;O'Donnell et al, 2017;Pont et al, 2018;Bakker et al, 2019;Stat et al, 2019;Nguyen et al, 2020;Oka et al, 2020). In our study, the residency time and degradation rate of nsDNA in the sponge tissues is an important factor that can hamper the detection of community patterns.…”
Section: Discussionmentioning
confidence: 80%